Single-cell transcriptomics and tissue metabolomics uncover mechanisms underlying wooden breast disease in broilers - Di Zhao; Zehe Song; Li Shen; Tian Xia; Qingyuan Ouyang; Haihan Zhang; Xi He; Kelang Kang (Poultry Science)
Accompanied by the accelerated growth rate of chickens, the quality of chicken meat has deteriorated in recent years. Wooden breast (WB) is a severe myopathy affecting meat quality, and its pathophysiology depends on gene expression and intercellular interactions of various cell types, which are not yet fully understood. We have performed a comprehensive transcriptomic and metabolomic atlas of chicken WB muscle. Our data showed a significant increase in the number of immune cells, WB muscle displayed a unique cluster of macrophages (cluster 11), distinct from the M1 and M2 macrophages. Regarding the myocytes, the most significant differences were the decrease in cell number and the intensification of fatty deposits. Satellite cells were involved in muscle repair and regeneration producing more collagen. Interestingly, the interaction network in the WB group was weaker compared to that in normal breast muscle. Additionally, we found six key differential metabolites across 22 pathways. When WB occurs, myocytes and endothelial cells undergo apoptosis, macrophages are activated and exert immune functions, satellite cells participate in muscle rebuilding and repair, and the content of metabolites undergoes significant changes. This cell transcriptome profile provides an essential reference for future studies on the development and remodeling of WB.